Knowledge, Communication, and Organizational Capabilities - Garicano, Luis; Wu, Yanhui (Organization Science, 2012)
This paper attempts to bridge a gap between organizational economics and strategy research through an analysis of knowledge and communication in organizations. We argue that organizations emerge to achieve the intensive use of the knowledge that is acquired to perform specific tasks and to integrate dispersed knowledge that is embodied in different human minds. The attributes of the tasks undertaken determine the optimal acquisition and distribution of knowledge. Depending on the codifiability of knowledge, different communication modes arise as a coordination mechanism to deepen the division of labor, leverage managerial talent, and exploit the increasing returns to knowledge. Organizational processes can be adapted through codes and culture to facilitate coordination; organizational structure can be designed to complement the limitations of human ability. We stress that organizational process and structure construct the core of organizational capital, which generates rent and sustains organizational growth. From the analysis, we draw implications for the strategic management of knowledge and human resources in organizations.